Uji Marshall Pada Campuran AC-WC Dengan Substitusi Filler - Zainal Abidin; Bunyamin Bunyamin; Febrina Dian Kurniasarir (Fakultas Teknik, 2021)
To improve the quality of pavement can be achieved by substituting filler materials. The materials used for mixing asphaltic concrete are Portland Cement (PC) Andalas type II and Krueng Neng Oyster Shell (ACT) to bind the aggregate with the mixture of asphalt becoming denser as the ACT contains silica and lime. The use of ACT as a filler is expected to improve the quality of the pavement mixture. The study aimed to determine the effect of Marshall Parameters on the use of PC-substituted ACT fillers with a composition of 0% ACT: 100% PC, 20% ACT: 80% PC, 50% ACT: 50% PC, 80% ACT: 20% PC , and 100% ACT: 0% PC against AC - WC mixture. The number of construction materials testing in this study was 66. The research method was Bina Marga 2010 Revision 4 of 2018. The results showed that all compositions met the requirements for the Bina Marga 2010 Revision 4 2018 specification, the best composition for ACT and PC filling substitutes were obtained a percentage of 20% ACT and 80% PC at 5.00% of the asphalt content, the stability value was 1323.01 kg with a VIM value of 3.66% VMA 15.91% VFA 76.99 and MQ 508.68 kg / mm.